(untitled) (Research, Society and Development, 2021)
Objectives: To discuss the impact of the COVID-19 pandemic on the food and nutrition security (FNS) of populations, showing the challenges faced and the emerging tactics of countries to prevent the expansion of food insecurity during and after this social and health crisis. Methodology: Narrative review carried out through a bibliographic search of articles in Portuguese and English, available in PubMed, Scielo, Embase and Lilacs databases. Articles published without publication deadline and which were available in full were included. The descriptors used were: “Food and nutrition security”, “Food insecurity”, “Pandemic” and “COVID-19”. Results: Procedures to control COVID-19 outbreaks affected food supply chains. In addition, high levels of unemployment, loss of income and rising food costs also hampered access to food, especially for the most socially vulnerable population. The processes of availability and access to food during the pandemic have had a direct impact on the population’s food choice, preparation and consumption. Consequently, government measures should help to promote FNS among populations, through the creation or expansion of social protection programs, distribution and improvement in access to food, protection of jobs and livelihoods, and support for small local producers. Conclusion: The actions promoted by governments must guarantee the FNS of populations, ensuring access to adequate and healthy food and aiming to reduce the negative impacts promoted by SARS-CoV-2 on the condition of food, health and nutrition of the population, especially the most vulnerable.